English Academic Writing for The Students of Widya Dharma University of Klaten - Anisa, Ike (International Journal of Active Learning, 2019)
English is an important that must be learn by the students in this time. Learning English in every skill is basic for the students to be mastery. Here, Writing is one of the main skill in learning English which is conclude on productive skill in the ability of producing language. In the university, writing  has the important role in mastering the complete skill of learning English especially in academic writing level. It has an aim that the students could write at least the  paper  in English. In the process of teaching and learning, it is found that the writing skill of the students was not satisfying. This research is described the problems faced by the students in mastering academic English writing in English education program of Widya Dharma University of Klaten.  In this research, the problems faced by the students is on the English vocabulary and the grammatical used in the sentences.